46.4k views
5 votes
What is the product of (x-2)(x+6)

User Plang
by
7.1k points

2 Answers

3 votes

Answer:

x²+4x−12

Explanation:

=(x+−2)(x+6)

=(x)(x)+(x)(6)+(−2)(x)+(−2)(6)

=x²+6x−2x−12

=x²+4x−12

- You multiply the first x and the first x in the second bracket

= x²

- You multiply the first x and the last number in the second bracket (6)

= 6x

-You multiply -2 and the first number of the second bracket x

= -2x

- You multiply both the last numbers in both of the brackets

= -2 x 6

= -12

then write it all out

=x²+6x−2x−12

=x²+ ( you have like terms so add them) -12

=x²+4x−12

User Intrepion
by
7.5k points
5 votes

hope it helped you:-)

thank you

What is the product of (x-2)(x+6)-example-1
User Firefog
by
7.6k points